Stiff competition for 52 teams vying to be the best in the game of handball organised by UMP - Siti Nurfarmy, Ibrahim (2019)
Universiti Malaysia Pahang (UMP) organised its Fourth UMP Handball East Coast Championship that reflected its forte in coordinating the tournament held since 2016. This year’s game was organised by UMP Handball Club and UMP Sports Centre with the support of Department of Student Affairs and Alumni (JHEPA). It was held on April 14, 2019.